PROBLEM-BASED LEARNING WITH CONCEPT MAP: IS IT EFFECTIVE TO IMPROVE METACOGNITIVE SKILLS? - Eka Putri Azrai, Rizhal Hendi Ristanto, Mulyaningsih (International Journal of Advanced Science and Technology, 2020)
Metacognitive skill is one of the skills that need to be developed in students, in the hope students can master the concept better so as to improve learning outcomes and improve the quality of education. The purpose of this study was to determine the effect of problem-based learning model with concept map on the metacognitive skill of senior high school students in biology learning of Ecosystem chapter. The method used is a quasi-experiment with pretest-posttest control group design. The population of this research is all students of grade X MIA at a Senior High School of Pandeglang, Indonesia. The sample used is X MIA 5 as the control class and X MIA 6 as an experimental class at a Senior High School Pandeglang, Indonesia. Sampling procedures was done by simple random sampling. Data of metacognitive skills was collected through the provision of metacognitive essay test as many as 10 questions. Essay test results were analyzed by metacognitive research rubric developed by Corebima. Based on the test results, the experimental class students’ metacognitive skills were in the category of can not really. The result of hypothesis testing by independent t-test showed a significance value of 0.000 < α (0.05), then reject Ho, which means there were significant effect of problem-based learning (PBL) model with concept map on metacognitive skill of students. Based on the results obtained from the results of this study concluded that metacognitive skills of students of a Senior High School in Pandeglang, Indonesia already begun but needs to be improved. Keywords: Concept map, ecosystem, metacognitive, problem-based learning